MENU TROPHIQUE DU GOÃ‰LAND LEUCOPHÃ‰E LARUS MICHAHELLIS DANS Lâ€™ÃŽLOT AGUÃ‰LI, ZONE HUMIDE DE RÃ‰GHAÃA - Ouarab, Samia; Talmat, Nora; Boukhemza, Mohamed; Doumandji, Salaheddine (European Scientific Journal, ESJ, 2014)
In Wetland Réghaïa more specifically on the island Agueli 1 km off the beach Réghaïa, we studied the diet of Gull Yellow-legged Larus michahellis during the breeding season. The analysis of 91 balls rejection has allowed us to recognize 52 prey species divided into 8 classes, 25 orders and 30 families. Number of prey fish in 2004 (AR = 33.9%) and birds in 2006 (AR = 21.2%) proved the most consumed. Yellow-legged Gulls in the study area also consumes arthropods, mammals, reptiles, plants and shellfish waste. This Laridé a very diversified diet (E = 0.89) in the wetland Réghaïa.